Lipophilicity profiling and cell viability assessment of a selected panel of endocrine disruptors. (February 2023) - Russo, Giacomo; Piccolo, Marialuisa; Neri, Ilaria; Ferraro, Maria Grazia; Santamaria, Rita; Grumetto, Lucia
Abstract: Endocrine disruptors are chemicals widely used worldwide by industries in a variety of applications. Routinely exposure to these chemicals, even if at low doses, can cause damage effects on human health. In the present study, we evaluated toxic effects of nine chemicals, among which phthalates, using various cell lines to inspect their capability to interfere with cell proliferation and viability. Alongside, we investigated their affinity for phospholipids to assess the possible passage through biomembranes. Experimentally determined logkw IAM.MG values ranged from 1.37 to 3.49 whilst calculated log kw IAM.DD2 spanned from 1.80 to 5.21, supporting the target contaminants to exhibit lipophilicity moderate or very high. The achieved results were related to pharmacokinetic and toxicological properties by ADMET predictor™ and EPI Suite™ software. Triclosan and 4-Nonylphenol were found to be the most toxic against all cell lines screened, showing an IC50 of 30 μM for triclosan on human keratinocytes and of 50 μM for 4-Nonylphenol on human colorectal adenocarcinoma cells. Overall, even if the phthalates showed higher IC50 values (ranging from 170 μM to 280 μM), we can assert that all contaminants herein tested were able to interfere with cell growth and viability. Graphical abstract: Image 1 Highlights: Cell viability assessment of five phthalates, two chlorobenzenes, 4-Nonylphenol and Triclosan. Endocrine disruptors biomembrane affinity evaluation using Immobilized Artificial Membrane Liquid Chromatography. Relationship between in silico prediction and biomimetic liquid chromatography data.